MitCOM-based prognostic model identifies GLUD1 as a key suppressor of glioblastoma growth and invasion through regulation of mitochondrial structure and metabolism - Yang Li; Chaoying Qin; Liangqi Jiang; Jun Su; Zhen Li; Qing Liu; Yuanbing Yao (Cancer Cell International)
Abstract Background Glioblastoma (GBM) is a highly aggressive brain tumour with a poor prognosis. Mitochondrial dysfunction, including changes in oxidative phosphorylation, reactive oxygen species (ROS) production, and cristae organisation, plays a key role in the progression of GBM. However, the role of mitochondrial protein complexes in GBM biology is poorly understood. Methods Bioinformatics analyses of GBM datasets and mitochondrial complexome profiling (‘MitCOM’) identified mitochondrial protein complex genes (MitCOMGs) with prognostic significance. A six-gene prognostic model was constructed using least absolute shrinkage and selection operator (LASSO) regression and validated in independent cohorts. GLUD1, the most significant gene, was further validated through in vitro assays, including Blue Native PAGE, metabolomic profiling, and various cell assays. Results GLUD1 expression was downregulated in GBM and associated with poor survival. Functional studies showed that GLUD1 regulates mitochondrial crista organisation and metabolic reprogramming. GLUD1 overexpression disrupted mitochondrial integrity, impaired respiratory chain complex assembly, and reduced adenosine triphosphate production. Metabolomic profiling revealed altered amino acid metabolism and tricarboxylic acid cycle intermediates that inhibited GBM cell proliferation and invasion. Conclusions GLUD1 is a key mitochondrial regulator in GBM, and its downregulation contributes to tumour progression through mitochondrial dysfunction and metabolic reprogramming. The six-gene MitCOMG model offers robust prognostic value and identified GLUD1 as a potential therapeutic target for GBM.